2018
DOI: 10.2217/nmt-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

A Report From the 8th Kuopio Alzheimer Symposium

Abstract: The international Kuopio Alzheimer Symposium was organized by the University of Eastern Finland in Kuopio, Finland on June 6-8, 2018 for the 8th time. Approximately 300 researchers in the fields of neuroscience and neurology from 12 different countries around the world gathered to Kuopio to hear and discuss about the latest insights into the mechanisms and comorbidities and novel approaches for diagnosis, prediction, prevention and therapies of Alzheimer's disease and other neurodegenerative diseases. The 2-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Currently, there are several ongoing clinical trials for potential new medications for AD (Table ). However, the latest news from many of these clinical trials indicated a high failure rate of many lead drug candidates, specifically the ones targeting β‐site APP cleaving enzyme 1 (BACE1) . Moreover, the elegant contributions from Cummings et al highlighted several small molecules BACE1 inhibitors that are currently in clinical trials for AD treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are several ongoing clinical trials for potential new medications for AD (Table ). However, the latest news from many of these clinical trials indicated a high failure rate of many lead drug candidates, specifically the ones targeting β‐site APP cleaving enzyme 1 (BACE1) . Moreover, the elegant contributions from Cummings et al highlighted several small molecules BACE1 inhibitors that are currently in clinical trials for AD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latest news from many of these clinical trials indicated a high failure rate of many lead drug candidates, specifically the ones targeting β-site APP cleaving enzyme 1 (BACE1). [7][8][9] Moreover, the elegant contributions from Cummings et al highlighted several small molecules BACE1 inhibitors that are currently in clinical trials for AD treatment. Around 26 candidates were introduced in clinical trials, including agents that target the amyloid-β (Aβ) protein through BACE1 inhibition and others as immunotherapies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It hasb een shownt hat in patients with AD, the serum levelso fA ChE and BChE are elevated to agreat extent,leadingtoanuncontrolled decreasei nt he levels of ACh, whichc auses an imbalance in motorc oordinationa nd, problems in cognition and memory. [10] Although the number of clinicalc andidates is high, there has also been as ubstantial declinei nn umbers progressing to the next level of evaluation, owing to the rise in toxicityconcerns and efficacy issues. [5] This intensifies the symptomsa ssociated with AD, and therefore AChE is ag ood target against which to develop potentiali nhibitors to bring equilibrium to the induced extreme levels of activity.Atpresent,four AChE inhibitor drugs are approved to treat the symptomatic effects of AD:t acrine, galantamine, donepezil, and rivastigmine.…”
Section: Introductionmentioning
confidence: 99%
“…Around 112d rug candidates were being tested in the clinicalp ipeline as of 2018, out of which,2 6c andidates were in phase III trials. [10] Although the number of clinicalc andidates is high, there has also been as ubstantial declinei nn umbers progressing to the next level of evaluation, owing to the rise in toxicityconcerns and efficacy issues.…”
Section: Introductionmentioning
confidence: 99%